Legalitas Retribusi Angkutan Laut Speed Boat Letti-Moa dan Lakor-Moa oleh Pemerintah Daerah Kabupaten Maluku Barat Daya - Dilmon Roger Lekidama; Saartje Sarah Alfons; Heillen Martha Yosephine Tita (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2022)
People has the right to receive services in the field of sea transportation, protection and legal certainty in accordance with applicable laws and regulations, so that the Regional Government stipulates Regional Regulation of Southwest Maluku Regency Number 7 of 2013 concerning Regional Retribution. This research used normative legal research. The results showed that Articles 87 to 92 of the Regional Regulation of Southwest Maluku Regency Number 7 of 2013 concerning Regional Retribution regulate Port Service Retribution and the party collecting the Levy that port service users must be provided with strong and sustainable services. The Levy against Speed Boad Owners of the Letti – Moa and Lakor – Moa routes is not facilitated with facilities and infrastructure in accordance with national shipping standards, resulting in harm to the community. The imposition of Speed Boad transportation service rates set by Speed Boat owners is not based on the provisions of valid laws and regulations. In terms of regional revenue, the authority to collect levies carried out by KPLP is contrary to Regional Regulations of Southwest Maluku Regency Number 7 of 2013 concerning Regional Retribution.